Totstandkoming van de grondwettelijke krachtlijnen voor een democratisch Zuid-Afrika - Pekane, Ted; Reyntjens, Filip (Afrika Focus, 1989)
Africa Focus publishes a Dutch translation of the "constitutional guidelines for a democratic South Africa", adopted in March 1988 at Lusaka, by the African National congress (ANC), together with a preface (by F.Reyntjens) and an extensive introduction written by Ted Pekane, member of the constitutional committee of the ANC, about the drafting of this important text. In the preface is referred to the political signification of a constitutional text in Africa today and to the more pragmatic content of the guidelines, compared to the Freedom Charter of 1955. T. Pekane explains the external factors that contributed to the drafting of the guidelines. He also points out the dangers of the "acceptable" models of constitution for the post-Apartheid period advanced by internal and external forces : a lot of those models are discreet options for a status-quo. KEYWORDS : African National Congress, constitution, politics, South Africa